Immunotherapy in Melanoma, Gastrointestinal (GI), and Pulmonary Malignancies - Dillon, Alexander B. (AIMS Public Health, 2015)
Oncologic immunotherapy involves stimulating the immune system to more effectively identify and eradicate tumor cells that have successfully adapted to survive the body's natural immune defenses. Immunotherapy has shown great promise thus far by prolonging the lives of patients with a variety of malignancies, and has added a crucial new set of tools to the oncologists' armamentarium. The aim of this paper is to provide an overview of immunotherapy treatment options that are currently available and under active research for melanoma, gastrointestinal (esophageal, gastric, pancreatic, and colorectal), and pulmonary malignancies. Potential biomarkers that may predict favorable responses to immunotherapies are discussed where applicable, as are future avenues of research in this rapidly evolving field.